Changes in horn size of Stone's sheep over four decades correlate with trophy hunting pressure. Issue 1 (8th February 2016) - Douhard, Mathieu; Festa‐Bianchet, Marco; Pelletier, Fanie; Gaillard, Jean‐Michel; Bonenfant, Christophe
Abstract: Selective harvest may lead to rapid evolutionary change. For large herbivores, trophy hunting removes males with large horns. That artificial selection, operating in opposition to sexual selection, can lead to undesirable consequences for management and conservation. There have been no comparisons of long‐term changes in trophy size under contrasting harvest pressures. We analyzed horn measurements of Stone's rams ( Ovis dalli stonei ) harvested over 37 years in two large regions of British Columbia, Canada, with marked differences in hunting pressure to identify when selective hunting may cause a long‐term decrease in horn growth. Under strong selective harvest, horn growth early in life and the number of males harvested declined by 12% and 45%, respectively, over the study period. Horn shape also changed over time: horn length became shorter for a given base circumference, likely because horn base is not a direct target of hunter selection. In contrast, under relatively lower hunting pressure, there were no detectable temporal trends in early horn growth, number of males harvested, or horn length relative to base circumference. Trophy hunting is an important recreational activity and can generate substantial revenues for conservation. By providing a reproductive advantage to males with smaller horns and reducing the availability of desirable trophies, however, excessive harvest may have the undesirable long‐term consequences of reducing both the harvest and the horn size of rams. These consequences can be avoided by limiting offtake.